Sampling interplanetary dust from Antarctic air. (27th May 2020) - Taylor, S.; Lever, J. H.; Burgess, K. D.; Stroud, R. M.; Brownlee, D. E.; Nittler, L. R.; Bardyn, A.; Alexander, C. M. O'D.; Farley, K. A.; Treffkorn, J.; Messenger, S.; Wozniakiewicz, P. J.
Abstract: We built a collector to filter interplanetary dust particles (IDPs) larger than 5 μm from the clean air at the Amundsen Scott South Pole station. Our sampling strategy used long duration, continuous dry filtering of near‐surface air in place of short duration, high‐speed impact collection on flags flown in the stratosphere. We filtered ~10 7 m 3 of clean Antarctic air through 20 cm diameter, 3 µm filters coupled to a suction blower of modest power consumption (5–6 kW). Our collector ran continuously for 2 years and yielded 41 filters for analyses. Based on stratospheric concentrations, we predicted that each month's collection would provide 300–900 IDPs for analysis. We identified 19 extraterrestrial (ET) particles on the 66 cm 2 of filter examined, which represented ~0.5% of the exposed filter surfaces. The 11 ET particles larger than 5 µm yield about a fifth of the expected flux based on >5 µm stratospheric ET particle flux. Of the 19 ET particles identified, four were chondritic porous IDPs, seven were FeNiS beads, two were FeNi grains, and six were chondritic material with FeNiS components. Most were <10 µm in diameter and none were cluster particles. Additionally, a carbon‐rich candidate particle was found to have a small 15 N isotopic enrichment, supporting an ET origin. Many other candidate grains, including chondritic glasses and C‐rich particles with Mg and Si and FeS grains, require further analysis to determine if they are ET. The vast majority of exposed filter surfaces remain to be examined.